The Use of Project-Based Learning to Foster Software Engineering Students’ English-Speaking Competence - Rifani Juliani; Rajji Koswara Adiredja; Anne Ratna Suminar (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to explore how Project-Based Learning (PjBL) is used in software engineering classrooms and how it can foster students’ English-speaking competence. This research employed a qualitative descriptive designing involving 40 eleventh-grade students from the Software Engineering (Rekayasa Perangkat Lunak) program and one English teacher at a vocational high school in Garut, Indonesia. Data were collected through classroom observations involving 40 students and one teacher, followed by semi-structured interviews with six selected students and the teacher. The findings revealed that PjBL was used through systematic stages, including starting with essential question, designing a project, scheduling, monitoring, assessing outcomes, and evaluating the experiences. The analysis reveals that PjBL functioned as a discourse-construction pedagogy, fostering students’ cohesion through the use of linking devices and improving coherence through logical organization of ideas during project presentations. Although some students still relied on memorization and faced vocabulary limitations and anxiety, continuous teacher scaffolding and feedback supported their gradual improvement. Thus, PjBL can foster students’ English-speaking competence by systematically strengthening discourse competence. However, as this study was limited to one vocational classroom with a small sample and focused only on discourse competence, further research with larger and more diverse participants and broader speaking competence aspects is needed to examine the wider applicability and long-term impact of PjBL.